CYBER INFLUENCE AND COGNITIVE THREATS - Benson, Vladlena, editor; McAlaney, John, editor (San Diego : Academic Press An imprint of Elsevier, 2020)
In the wake of fresh allegations that personal data of Facebook users have been illegally used to influence the outcome of the US general election and the Brexit vote, the debate over manipulation of social Big Data continues to gain more momentum. Cyber Influence and Cognitive Threats addresses various emerging challenges in response to cybersecurity, examining cognitive applications in decision-making, behaviour and basic human interaction. The book examines the role of psychology in cybersecurity by addressing each factor involved in the process: hackers, targets, cybersecurity practitioners, and the wider social context in which these groups operate. Cyber Influence and Cognitive Threats covers a variety of topics including information systems, psychology, sociology, human resources, leadership, strategy, innovation, law, finance and others. -Explains psychological factors inherent in machine learning and artificial intelligence. -Explores attitudes towards data and privacy through the phenomena of digital hoarding and protection motivation theory. -Discusses the role of social and communal factors in cybersecurity behaviour and attitudes. -Investigates the factors that determine the spread and impact of information and disinformation.